Teaching as bodily enactment: relational formations of touch and movement. Issue 5 (3rd September 2022) - Todd, Sharon
ABSTRACT: This paper explores a common representational form of teaching that has reappeared in current educational theory: the figure of the teacher as one who points. Informed by Nicolas Bourriaud's notion of relational aesthetics I outline how the form of pointing is actually a relational formation that invites students into certain relationships with objects of study as well as with teachers themselves. Focusing on relational encounters as central to teaching, I argue in the second part of the paper that movement and the dynamics of touch are key to reframing teaching as bodily enactment. Drawing on the work of Erin Manning, I explore how movement and touch are generative of educational relations and how they enable students and teacher to co-create educational spaces together. Teaching as bodily enactment enables us to understand how physical bodies matter in and to our educational practices as well as our representations of them.